Long-Term Outcomes Comparison of Endoscopic Resection With Gastrectomy for Treatment of Early Gastric Cancer: A Systematic Review and Meta-Analysis - An, Liangliang; Gaowa, Sharen; Cheng, Haidong; Hou, Mingxing (Frontiers in Oncology, 2019)
Background: Endoscopic resection (ER) and gastrectomy both have been accepted as curative treatments for early gastric cancer. We intend to compare ER with gastrectomy treatment on safety of patients, disease-free survival and overall survival for early gastric cancer through this systematic review. Methods: A literature search was performed in Pubmed, Embase, and Cochrane Library databases. Studies that have compared ER with gastrectomy for early gastric cancer were included in this meta-analysis. We searched for clinical studies published before March 2019. Stata 12.0 software was used for systematic analysis. Results: Nine studies were included in this systematic review, ER treatment was associated with a shorter length of stay (WMD = -8.53, 95% CI -11.56 to -5.49), fewer postoperative complication (OR = 0.47, 95% CI 0.34 to 0.65). ER can be performed safely with shorter hospital stay and fewer postoperative complications than gastrectomy. Recurrence rate was higher for ER than for gastrectomy treatment (HR = 3.56, 95% CI 1.86 to 6.84), mainly because metachronous gastric cancers developed only in the ER treatment. However, most of the metachronous gastric cancers could be curatively treated with ER again, and it didn’t affect overall survival of patients with early gastric cancer. There was no difference in overall survival rate between ER and gastrectomy (HR = 0.84, 95% CI 0.63 to 1.13). Conclusions: Due to the comparable overall survival and lower postoperative complications and shorter length of stay, ER is as acceptable as gastrectomy for early gastric cancer, who met the indication for ER treatment.